2011
DOI: 10.3147/jsfp.46.108
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a Combined Vaccine against Edwardsiella tarda, Streptococcus iniae and Streptococcus parauberis in Farmed Olive Flounder Paralichthys olivaceus

Abstract: 魚病研究 F i s h P a t h o l o g y , 4 6 (4) ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In addition to S. agalactiae and S. iniae, other Streptococcus bacteria are also emerging as important pathogens in aquaculture. For example, Streptococcus dysgalactiae is responsible for disease outbreaks in trout, sturgeon, amberjack and yellowtail [157][158][159], and S. phocae is the causative agent of repeated disease outbreaks in cage-farmed Atlantic salmon in Chile since 1999, with mortality up to 25% [160][161][162]. Currently, no vaccine is commercially available to protect fish from infections by S. dysgalactiae or S. phocae.…”
Section: Haemorrhagic Septicaemiamentioning
confidence: 99%
“…In addition to S. agalactiae and S. iniae, other Streptococcus bacteria are also emerging as important pathogens in aquaculture. For example, Streptococcus dysgalactiae is responsible for disease outbreaks in trout, sturgeon, amberjack and yellowtail [157][158][159], and S. phocae is the causative agent of repeated disease outbreaks in cage-farmed Atlantic salmon in Chile since 1999, with mortality up to 25% [160][161][162]. Currently, no vaccine is commercially available to protect fish from infections by S. dysgalactiae or S. phocae.…”
Section: Haemorrhagic Septicaemiamentioning
confidence: 99%
“…Nya and Austin (2009a) showed that dietary inclusion of 0.5% and 1% garlic effectively lowered mortality of rainbow trout infected with Aeromonas hydrophila. A combined vaccine containing formalin-inactivated Edwardsiella tarda, Streptococcus iniae, and S. parauberis successfully induced humoral and protective immunity in olive flounder (Han et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The total value of olive flounder aquaculture production in 2011 was estimated at US $484.8 million (Food and Agriculture Organization of the United Nations, FAO, http://www.fao.org). However, a major cause of loss of stock in olive flounder aquaculture operations are infectious bacterial diseases, streptococcosis and edwardsiellosis (Han et al, 2011). These bacterial infections in olive flounder have produced serious outbreaks, with chronic disease and high mortality (Matsuyama et al, 1992;Eldar et al, 1999;Nguyen et al, 2002).…”
Section: Introductionmentioning
confidence: 99%